Boys in a famous choir: Singing and ticcing. Issue 6 (20th December 2017) - Tunc, Sinem; Münchau, Alexander
Abstract : This informal observational study on the tic prevalence in 40 young singers was carried out during a public concert of Bach's Christmas Oratorio. Tics were highly prevalent (present in 35% = 14 boys). Given the possibility of an overrepresentation of perioral tics in this group of highly achieving young vocal artists, one might speculate that there is a relationship between the ability of the motor system to produce a surplus of movements (tics) and high performance (exquisite singing). Despite the unusual study design, with all its limitations, our observations strengthen the view that tics may be related to motor learning. However, alternative explanations, for example, that repetitive motor performance or personality traits in singers drive tic development, could also be true. In light of the boys choir's enchantment, the sole perception of tics as a disorder falls short of the properties of the motor system. Ann Neurol 2017;82:1029–1031